The Politeness of English Teacher's Utterances Inside and Outside Classroom - Ceriyantina, Dian Tri (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
ABSTRACT Ceriyantina,D.T. The Politeness of Teacher’s Utterance Inside and Outside The Learning Process. Final Project. English Department, Faculty of Language and Arts, Semarang State University. Advisor: Dr. Hendi Pratama,M.A Keyword: Politeness, Utterance, Pragmatic, Teacher. This study is about politeness of the teacher’s utterance entitled: The Politeness of Teacher’s Utterances Inside and Outside The Learning Process. The aim of this study is to find out the strategy and the dominant maxim of politeness that used by teacher inside and outside the learning process. This study was a descriptive qualitative study to describe the result of the analyzing of teacher’s utterance. I used teacher’s utterance inside and outside the learnig process as the object of the study. In collecting data, i record the teacher’s utterance inside the learning process then transcript the result of the record. After that, the data will be analyzed with the type of pooliteness and clasified into the maxim of politeness. The result of the analyze teacher’s utterance inside the learning process contain pf 73 utterances with ten maxims of politeness by Leech (2014). After going through data analysis process, it can be concluded that seven maxims of politeness used by English teacher inside the learning process. The maxims that used are Tact with percentage 47,95%, Obligation S to O with percentage 27,29%, Generosity with percentage 17,80%, Approbation with percentage 2,74%, Modesty with percentage 1,37%, Obligation O to S with percentage 1,37%, Sympathy with percentage 1,37%. Meanwhile, the result of the analyze teacher’s utterance outside the learning process contain of 20 utterance with five maxims, the maxim that used are Tact with percentage 50%, Generosity with percentage 15%, Modesty with percentage 15%, Approbation with percentage 10%, Obligation os S to O with percentage 10%. Based on the result of the procedure, the writer cab conclude that the dominant type of the maxim that used by English teacher inside and outside the learning process. The writer also use analysis method to analyze the data so that can be found the reason of the classification result.